1999
DOI: 10.1016/s0002-9440(10)65430-2
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Inhibition of Retinal and Choroidal Neovascularization by Oral Administration of a Kinase Inhibitor

Abstract: The most common cause of new blindness in young patients is retinal neovascularization , and in the elderly is choroidal neovascularization. Therefore, there has been a great deal of attention focused on the development of new treatments for these disease processes. Previous studies have demonstrated partial inhibition of retinal neovascularization in animal models using antagonists of vascular endothelial growth factor or other signaling molecules implicated in the angiogenesis cascade. These studies have ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 32 publications
7
113
1
Order By: Relevance
“…[1][2][3][4] These data suggest that the VEGF pathway may be an important therapeutic target and results from clinical trials using an aptamer 5 or an antibody fragment 6 that binds VEGF-A have supported this contention. Blocking VEGF receptors is another strategy for antagonizing VEGF-A that has the potential advantage of blocking multiple VEGF family members at once.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These data suggest that the VEGF pathway may be an important therapeutic target and results from clinical trials using an aptamer 5 or an antibody fragment 6 that binds VEGF-A have supported this contention. Blocking VEGF receptors is another strategy for antagonizing VEGF-A that has the potential advantage of blocking multiple VEGF family members at once.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recurrent neovascularization and permanent visual loss occur in the majority of patients who initially have had successful treatment (7).…”
Section: Introductionmentioning
confidence: 99%
“…9 -13 Somewhat surprisingly (because hypoxia is not known to play a role), VEGF signaling was also found to be necessary for development of choroidal neovascularization in a murine model. 12,14 Although these studies clearly implicated VEGF as a stimulatory factor for ocular neovascularization, other studies showed that in some situations expression of VEGF by itself was insufficient to induce retinal neovascularization. The retinas of patients with nonproliferative diabetic retinopathy or other retinal diseases may show elevated levels of VEGF without retinal neovascularization.…”
mentioning
confidence: 99%